2020
DOI: 10.1111/bcp.14502
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin use and risk of head and neck cancer—A Danish nationwide case–control study

Abstract: Results concerning a potential preventive effect of aspirin on head and neck cancer (HNC) are conflicting. We examined the association between low‐dose aspirin use and HNC risk overall and by degree of human papillomavirus association in a nested case–control study using nationwide registries. Cases (n = 12 389) were all Danish residents diagnosed with primary HNC (2000–2015). Age‐ and sex‐matched population controls (n = 185 835) were selected by risk‐set‐sampling. Using conditional logistic regression, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In head and neck cancer patients, evaluation of aspirin as a chemopreventive agent is still controversial. A hospital-based case control study revealed that aspirin use can reduce head and neck cancer risk ( 170 ), whereas the other investigations demonstrated that there was no significant correlation between aspirin intake and head and neck cancer ( 171 , 172 ). Moreover, the risk of gastrointestinal bleeding could limit the use of aspirin for cancer prevention and/or treatment ( 29 , 30 ).…”
Section: Targeting Platelet-tumor Interaction For Chemotherapymentioning
confidence: 99%
“…In head and neck cancer patients, evaluation of aspirin as a chemopreventive agent is still controversial. A hospital-based case control study revealed that aspirin use can reduce head and neck cancer risk ( 170 ), whereas the other investigations demonstrated that there was no significant correlation between aspirin intake and head and neck cancer ( 171 , 172 ). Moreover, the risk of gastrointestinal bleeding could limit the use of aspirin for cancer prevention and/or treatment ( 29 , 30 ).…”
Section: Targeting Platelet-tumor Interaction For Chemotherapymentioning
confidence: 99%